The Relations Between Communication Competence of Salesman and Information Exposure from Autonetmagz Youtube Channel with Buying Decision of Honda City in Semarang City - Firdaus Irfan Harish; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The four-wheeled industry competition requires salesperson roles who is competent in communicating to persuade prospective consumers to do the purchasing decision, besides exposure to information that was provided to new media as a channel YouTube Autonetmagz considered could affect prospective consumers do purchase decisions against the Honda City. This research aims to proofing the relationship of communication competence of salespeople and exposure information Autonetmagz Youtube Channel with the purchasing decision of Honda City, using non-probability sampling techniques and accidental sampling technuques, with a population of sample taken as many as 50 people respondents townspeople semarang with the provisions ever communicate with Honda salespeople and had also been watching the channels Autonetmagz The first hypothesis test results it is known that there is a positive relationship between the variable competence communication salespeople with variable purchasing decisions of Honda City in the city of Semarang, With use speech act theories can be proven through analysis of Kendall's Tau correlation produce, numbers of significance of 0.003 or revealed highly significant correlation coefficients and value of the correlation coefficient in which the value 0377 0.26 to 0.50 stated has a close correlation enough. Meanwhile on the second hypothesis in mind that there is a positive relationship between the variable information terapaan Autonetmagz Youtube Channel with variable purchasing decisions of Honda City in the city of Semarang, with with new media theory can be proven through the analysis of correlation Kendall's Tau produce numbers of significance of 0.000 revealed highly significant correlation coefficients and values of correlation coefficients where 0435 worth 0.26 to 0.50 stated has a close correlation enough.